Chemical plating solution, preparation method of chemical plating solution, Ni-P-Gr chemical plating layer and preparation method and application of Ni-P-Gr chemical plating layer
By homogenizing and ultrasonic dispersion in the electroless plating solution, the problem of insufficient dispersion uniformity of graphene oxide is solved, and the hardness, wear resistance and binding force of the Ni-P-Gr electrolytic plating layer are improved.
Patent Information
- Application Number
- CN202411526910.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
In the existing electroless plating process, the dispersion uniformity of graphene oxide is insufficient, resulting in poor hardness, wear resistance and binding strength of the plating layer.
By mixing nickel sulfate, sodium citrate, sodium acetate, sodium hypophosphite, graphene oxide and deionized water, the pH value is adjusted to 4 to 4.5, a basic plating solution is formed, and then mixed with sodium dodecylbenzenesulfonate Perform homogenization and ultrasonic dispersion to prepare an electroless plating solution with uniform dispersion of graphene oxide.
Good dispersion of graphene oxide in Ni-P-Gr electroless plating is achieved, and the hardness, wear resistance and bonding force of the plating are improved.
Smart Images

Figure CN119392227A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical plating, and in particular to a chemical plating solution and a preparation method thereof, a Ni-P-Gr chemical plating layer and a preparation method and application thereof. Background Art
[0002] Martensitic stainless steel is a traditional hardenable cast steel grade. The Cr content in this type of steel is not less than 13%, and the carbon content is between 0.1% and 0.4%. The elements usually added are Ni, Cr, Si, Mn, Mo, V, etc. Due to its high hardness, high strength, excellent wear resistance and corrosion resistance, it is widely used in machinery, shipbuilding, aerospace, automobile and other industries. The carbon content has a significant impact on the performance of steel. According to the different carbon contents, martensitic stainless steel can be divided into three levels: low carbon martensitic stainless steel (such as 1Cr12 and 1Cr13), medium carbon martensitic stainless steel (such as 2Cr12 and 4Cr13) and high carbon martensitic stainless steel (such as 9Cr18 and 9Cr18MoV, etc.). Among them, the ultra-low carbon martensitic stainless steel 0Cr13Ni5Mo stainless steel has excellent performance in casting, welding and machining process performance and service performance. It is often used as the material for the runner blades, upper crowns and lower rings of large turbines in power stations such as Yantan and Three Gorges, so it has important development and use value. Since hydraulic machinery will suffer varying degrees of damage in multiphase flow, it is particularly important to study its surface treatment methods to solve its wear resistance problem.
[0003] In order to improve the corrosion resistance of stainless steel and make up for its relatively low wear resistance, the methods currently used to enhance the wear resistance of stainless steel include physical vapor deposition (PVD), chemical vapor deposition (CVD), ion implantation, laser cladding, plasma surface treatment, thermal spraying technology, electroplating and chemical plating. Among them, chemical nickel plating technology is favored due to its corrosion resistance, wear resistance and uniform coating. In addition, it is known for its simple process and is easier to achieve large-scale industrial production. Therefore, chemical plating technology is regarded as a stainless steel surface treatment process with broad application prospects.
[0004] As a special two-dimensional material, graphene is well-known for its excellent conductivity, stable chemical properties and excellent mechanical strength. Its application range has expanded to many fields such as hydrogen storage, composite materials, energy batteries, etc. With the advancement and improvement of graphene preparation technology, the potential applications of graphene are constantly being explored and expanded. Introducing graphene in the chemical plating process can bring into play the synergistic effect of graphene and metal plating.
[0005] The prior art discloses the effect of adding different concentrations of graphene (50-250 mg / L) to the chemical Ni-P alloy plating solution on the wear resistance of the Ni-P-Gr composite coating on the surface of 45 steel. After experimental testing, when the content of graphene in the plating solution is 100 mg / L, the surface of the composite coating achieves the best smoothness and density, and also shows good wear resistance. However, when the mass concentration of graphene in the plating solution increases to 150 mg / L, the grains on the surface of the coating slightly agglomerate. Continuing to increase the mass concentration of graphene in the plating solution, the agglomeration phenomenon of the composite coating worsens.
[0006] The prior art discloses the use of pure copper as a matrix material, and the preparation of nickel-phosphorus-graphene chemical composite coatings with different graphene contents by chemical composite plating process, and the analysis of the structure, hardness, wear resistance and corrosion resistance of the coating by various testing methods. Research data show that the Ni-P chemical composite coating with added graphene has better surface smoothness, flatness and density than the pure Ni-P coating, and also has stronger bonding force with the substrate. The addition of graphene enhances the microhardness, wear resistance and corrosion resistance of the coating, and when the graphene addition amount is 40mg / L, the comprehensive performance of the composite coating is the best. However, when the graphene addition amount is 60mg / L, it can be seen that some graphene has agglomerated.
[0007] The prior art discloses the preparation of graphene-nickel-phosphorus chemical composite coating on 45 steel, and studies the effect of different graphene addition amounts on the abrasion performance and mechanism of the composite coating in 3.5% NaCl solution. The study shows that when the graphene addition amount is 100 mg / L, the wear resistance of the composite coating is optimal, and the promoting effect of corrosion on wear accounts for more than 93% of the interaction. However, when the graphene addition amount is 200 mg / L and 250 mg / L, the graphene addition amount is too large, agglomeration will occur, the composite coating structure is not dense, and under the external force of the friction head, cracks appear in the composite coating, and the internal structure is destroyed.
[0008] The prior art discloses a method for preparing glass with a graphene oxide nickel-phosphorus composite coating, wherein a glass substrate that has been degreased, decontaminated, roughened, and activated is immersed in a graphene oxide nickel-phosphorus chemical plating solution for 20 to 30 minutes, then rinsed with distilled water and dried. However, the dispersion uniformity of graphene oxide in the graphene oxide nickel-phosphorus composite coating is not good enough.
[0009] It can be seen that the dispersion uniformity of graphene in the coating prepared by the existing chemical plating process is not good enough. Summary of the invention
[0010] In view of this, the object of the present invention is to provide a chemical plating solution and a preparation method thereof, a Ni-P-Gr chemical plating layer and a preparation method and application thereof. In the Ni-P-Gr chemical plating layer prepared by using the chemical plating solution provided by the present invention, graphene oxide is evenly dispersed, the Ni-P-Gr chemical plating layer has high hardness, good wear resistance, and strong bonding force with the substrate.
[0011] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0012] The present invention provides a method for preparing a chemical plating solution, comprising the following steps:
[0013] Mix nickel sulfate, sodium citrate, sodium acetate, sodium hypophosphite, graphene oxide and deionized water, and adjust the pH value to 4-4.5 to obtain a basic plating solution; the content of graphene oxide in the basic plating solution is 0.1-0.4 g / L;
[0014] The base plating solution is mixed with sodium dodecylbenzene sulfonate, homogenized and then ultrasonically dispersed to obtain a chemical plating solution; the power of the ultrasonic dispersion is 100 to 180 W, and the time is 35 to 55 minutes.
[0015] Preferably, the composition of the basic plating solution includes: 25-35 g / L nickel sulfate, 8-12 g / L sodium citrate, 15-25 g / L sodium acetate, 15-25 g / L sodium hypophosphite, 0.1-0.4 g / L graphene oxide, and the solvent is deionized water;
[0016] The graphene oxide is soaked in deionized water before use.
[0017] Preferably, the homogenization process is carried out at a rotation speed of 12000 to 16000 r / min and for a time of 10 to 15 min.
[0018] The present invention also provides a chemical plating solution prepared by the preparation method described in the above technical solution, wherein the content of graphene oxide in the chemical plating solution is 0.1 to 0.4 g / L.
[0019] Preferably, the composition of the chemical plating solution includes: 25-35 g / L nickel sulfate, 8-12 g / L sodium citrate, 15-25 g / L sodium acetate, 15-25 g / L sodium hypophosphite, 0.1-0.4 g / L graphene oxide, 0.4-0.5 g / L sodium dodecylbenzene sulfonate, and the solvent is deionized water.
[0020] The present invention also provides a method for preparing a Ni-P-Gr chemical plating layer, comprising the following steps:
[0021] The substrate is placed in the chemical plating solution described in the above technical solution to perform chemical plating to form a Ni-P-Gr chemical plating layer on the surface of the substrate.
[0022] Preferably, the substrate comprises a stainless steel substrate or a carbon steel substrate;
[0023] The stainless steel substrate includes a martensitic stainless steel substrate, an austenitic stainless steel substrate or a ferritic stainless steel substrate;
[0024] The stainless steel substrate is first subjected to acid-base degreasing, sensitization treatment, activation treatment and reduction treatment in sequence before use;
[0025] The sensitizing solution used in the sensitization treatment includes SnCl2, HCl aqueous solution and deionized water, the content of SnCl2 in the sensitizing solution is 8-12 g / L, and the volume ratio of HCl aqueous solution to deionized water is 7-9:1; the temperature of the sensitization treatment is room temperature, and the time is 4-6 minutes;
[0026] The activation solution used in the activation treatment includes PdCl2, ethanol and deionized water, the content of PdCl2 in the activation solution is 0.3-0.6 g / L, and the volume ratio of ethanol to deionized water is 2-3:1; the temperature of the activation treatment is room temperature, and the time is 1.5-2.5 min;
[0027] The reducing solution used in the reduction treatment includes sodium hypophosphite and deionized water, and the content of sodium hypophosphite in the reducing solution is 25-35 g / L; the temperature of the reduction treatment is room temperature, and the time is 30 seconds.
[0028] Preferably, the temperature of the chemical plating is 70-90° C., the time is 2-3 hours, and the chemical plating is performed under stirring conditions.
[0029] The present invention also provides a Ni-P-Gr chemical plating layer obtained by the preparation method described in the above technical solution.
[0030] The present invention also provides the application of the Ni-P-Gr chemical plating layer described in the above technical solution in the field of metal surface modification.
[0031] The present invention provides a method for preparing a chemical plating solution, comprising the following steps: mixing nickel sulfate, sodium citrate, sodium acetate, sodium hypophosphite, graphene oxide and deionized water, adjusting the pH value to 4.2, and obtaining a basic plating solution; the content of graphene oxide in the basic plating solution is 0.1-0.4 g / L; mixing the basic plating solution with sodium dodecylbenzene sulfonate, performing homogenization treatment and ultrasonic dispersion to obtain a chemical plating solution; the power of the ultrasonic dispersion is 100-180 W, and the time is 35-55 min. The present invention uses homogenization treatment and ultrasonic dispersion in the process of preparing the chemical plating solution, and controls the addition amount of graphene oxide and the power and time of ultrasonic dispersion, so that the graphene oxide in the prepared chemical plating solution has good dispersion uniformity, the graphene oxide in the Ni-P-Gr chemical plating layer formed by the chemical plating solution prepared by the present invention has good dispersion, the Ni-P-Gr chemical plating layer has high hardness, good wear resistance, and strong bonding with the substrate.
[0032] Furthermore, the preparation method of the chemical plating solution provided by the present invention has simple process, simple operation, low cost and is suitable for industrial production.
[0033] Moreover, the preparation method of the Ni-P-Gr chemical plating layer provided by the present invention has simple process and low cost, and the prepared Ni-P-Gr chemical plating layer has high hardness, good wear resistance, and strong bonding force with the substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Macroscopic structural images of Ni-P-Gr chemical plating layers prepared under different ultrasonic powers and times, including: a) 180W / 35min; b) 180W / 45min; c) 140W / 35min, d) 140W / 45min; e) 100W / 35min, f) 100W / 45min; g) 180W / 55min; h) 140W / 55min; i) 100W / 55min;
[0035] Figure 2 The XRD diffraction pattern of Ni-P-Gr chemical plating layer with ultrasonic power of 140W and ultrasonic time of 35min;
[0036] Figure 3 The cross-sectional SEM morphology of Ni-P-Gr chemical plating layer under different ultrasonic powers and times, among which the left picture is 140W / 45min; the right picture is 100W / 35min;
[0037] Figure 4 The element diffraction peak intensity distribution diagram of the cross section of the Ni-P-Gr chemical plating layer under different ultrasonic powers and times, where the left figure is 140W / 45min; the right figure is 100W / 35min;
[0038] Figure 5 The microhardness diagram of Ni-P-Gr chemical plating under different ultrasonic power and time;
[0039] Figure 6 The samples with cracks and bubbles in the thermal shock test, the left picture is 180W / 45min; the right picture is 180W / 55min;
[0040] Figure 7 The macroscopic morphology of the Ni-P-Gr chemical plating layer with different graphene oxide addition amounts. From left to right, the graphene oxide addition amounts are 0.1g / L, 0.2g / L, 0.3g / L and 0.4g / L;
[0041] Figure 8 The surface morphology of Ni-P-Gr chemical plating with different graphene oxide addition amounts taken by AX10 metallographic microscope. The left picture in the first row is 0.1g / L, the right picture is 0.2g / L, the left picture in the second row is 0.3g / L, and the right picture is 0.4g / L.
[0042] Fig. 9 The cross-sectional SEM morphology of Ni-P-Gr chemically plated coatings with different graphene oxide addition amounts, the first row of left pictures are 0.1 g / L, the right pictures are 0.2 g / L, the second row of left pictures are 0.3 g / L, the right pictures are 0.4 g / L;
[0043] Fig.10 The EDS thermal field spectrum image and element distribution map of Ni-P-Gr chemical plating layer with a graphene oxide addition amount of 0.1g / L;
[0044] Fig.11 The EDS thermal field spectrum image and element distribution map of Ni-P-Gr chemical plating layer with a graphene oxide addition amount of 0.2g / L;
[0045] Fig.12 The EDS thermal field spectrum image and element distribution map of Ni-P-Gr chemical plating layer with graphene oxide addition of 0.3g / L;
[0046] Fig.13 The EDS thermal field spectrum image and element distribution map of Ni-P-Gr chemical plating layer with a graphene oxide addition of 0.4g / L;
[0047] Fig.14 The microhardness diagram of the surface of Ni-P-Gr chemical plating layer with different addition amounts of graphene oxide;
[0048] Fig.15The wear microstructures of Ni-P-Gr chemically plated coatings with different graphene oxide addition amounts, where the left picture in the first row is 0.1g / L, the right picture is 0.2g / L, the left picture in the second row is 0.3g / L, and the right picture is 0.4g / L;
[0049] Fig.16 The graph showing the variation of the friction coefficient of the Ni-P-Gr chemically plated coating with different addition amounts of graphene oxide versus the abrasion time;
[0050] Fig.17 This is a comparison of the weight loss before and after friction and wear of Ni-P-Gr chemical plating with different amounts of graphene oxide added. DETAILED DESCRIPTION
[0051] The present invention provides a method for preparing a chemical plating solution, comprising the following steps:
[0052] Mix nickel sulfate, sodium citrate, sodium acetate, sodium hypophosphite, graphene oxide and deionized water, and adjust the pH value to 4-4.5 to obtain a basic plating solution; the content of graphene oxide in the basic plating solution is 0.1-0.4 g / L;
[0053] The base plating solution is mixed with sodium dodecylbenzene sulfonate, homogenized and then ultrasonically dispersed to obtain a chemical plating solution; the power of the ultrasonic dispersion is 100 to 180 W, and the time is 35 to 55 minutes.
[0054] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0055] The invention mixes nickel sulfate, sodium citrate, sodium acetate, sodium hypophosphite, graphene oxide and deionized water, and adjusts the pH value to 4-4.5 to obtain a basic plating solution; the content of graphene oxide in the basic plating solution is 0.1-0.4 g / L.
[0056] In the present invention, the mixing of nickel sulfate, sodium citrate, sodium acetate, sodium hypophosphite, graphene oxide and deionized water preferably includes: dissolving nickel sulfate, sodium citrate, sodium acetate, sodium hypophosphite and graphene oxide in deionized water respectively to obtain nickel sulfate solution, sodium citrate solution, sodium acetate solution, sodium hypophosphite solution and graphene oxide solution respectively; pouring the nickel sulfate solution into the sodium citrate solution and stirring evenly, adding the sodium acetate solution and stirring evenly, adding the sodium hypophosphite solution and stirring evenly, adding the graphene oxide and stirring evenly. In the present invention, the concentrations of the nickel sulfate solution, sodium citrate solution, sodium acetate solution, sodium hypophosphite solution and graphene oxide are preferably determined according to the concentrations of nickel sulfate, sodium citrate, sodium acetate, sodium hypophosphite and graphene oxide in the base plating solution.
[0057] In the present invention, the graphene oxide is soaked in deionized water before use. The soaking temperature is preferably room temperature. The soaking time is ≥20 h, more preferably 20 to 30 h, and in a specific embodiment of the present invention, it is 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h or 30 h.
[0058] In the present invention, the composition of the basic plating solution preferably includes: nickel sulfate 25-35g / L, which can be 25g / L, 26g / L, 27g / L, 28g / L, 29g / L, 30g / L, 31g / L, 32g / L, 33g / L, 34g / L or 35g / L in a specific embodiment of the present invention; sodium citrate 8-12g / L, which can be 8g / L, 8.5g / L, 9g / L, 9.5g / L, 10g / L, 10.5g / L, 11g / L, 11.5g / L or 12g / L in a specific embodiment of the present invention; sodium acetate 15-25g / L, which can be 15g / L, 16g / L, 17g / L, 18g / L, 19g / L, 20g / L, 21g / L, 22g / L, 23g / L, 24g / L, 25g / L 15-25 g / L of sodium hypophosphite, which can be 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L, 20 g / L, 21 g / L, 22 g / L, 23 g / L, 24 g / L or 25 g / L in specific embodiments of the present invention; 0.1-0.4 g / L of graphene oxide, which can be 0.1 g / L, 0.15 g / L, 0.2 g / L, 0.25 g / L, 0.3 g / L, 0.35 g / L or 0.4 g / L in specific embodiments of the present invention.
[0059] In the present invention, the acid used to adjust the pH value preferably includes an aqueous solution of HCl; the concentration of the aqueous solution of HCl is preferably 12 mol / L. In a specific embodiment of the present invention, the pH value may be 4, 4.1, 4.2, 4.3, 4.4 or 4.5.
[0060] After obtaining the basic plating solution, the present invention mixes the basic plating solution with sodium dodecylbenzene sulfonate, performs homogenization treatment and then ultrasonically disperses the mixture to obtain a chemical plating solution; the power of the ultrasonic dispersion is 100 to 180 W, and the time is 35 to 55 minutes.
[0061] In the present invention, the content of sodium dodecylbenzenesulfonate in the chemical plating solution is preferably 0.4-0.5 g / L, and in specific embodiments of the present invention, it can be 0.41 g / L, 0.42 g / L, 0.43 g / L, 0.44 g / L, 0.45 g / L, 0.46 g / L, 0.47 g / L, 0.48 g / L, 0.49 g / L or 0.5 g / L.
[0062] In the present invention, the rotation speed of the homogenization treatment is preferably 12000-16000 r / min, and in a specific embodiment of the present invention, it can be 12000 r / min, 13000 r / min, 14000 r / min, 15000 r / min or 16000 r / min; the time of the homogenization treatment is preferably 10-15 min, and in a specific embodiment of the present invention, it can be 10 min, 11 min, 12 min, 13 min, 14 min or 15 min.
[0063] In the present invention, the power of the ultrasonic dispersion is 100-180 W, and in a specific embodiment of the present invention, it can be 100 W, 110 W, 120 W, 130 W, 140 W, 150 W, 160 W, 170 W or 180 W; the time of the ultrasonic dispersion is 35-55 min, and in a specific embodiment of the present invention, it can be 35 min, 36 min, 37 min, 38 min, 39 min, 40 min, 41 min, 42 min, 43 min, 44 min, 45 min, 46 min, 47 min, 48 min, 49 min, 50 min, 51 min, 52 min, 53 min, 54 min or 55 min.
[0064] The structure and performance of the chemical plating layer will be affected by different process conditions. The present invention can ensure that the graphene oxide is well dispersed in the chemical plating solution by controlling the addition amount of graphene oxide and the power and time of ultrasonic dispersion, thereby ensuring that the graphene oxide in the prepared Ni-P-Gr chemical plating layer has good dispersion. The Ni-P-Gr chemical plating layer has high hardness, good wear resistance, and strong bonding with the substrate.
[0065] The present invention also provides a chemical plating solution prepared by the preparation method described in the above technical solution, wherein the content of graphene oxide in the chemical plating solution is 0.1 to 0.4 g / L.
[0066] In the present invention, the composition of the chemical plating solution preferably includes: 25-35 g / L nickel sulfate, 8-12 g / L sodium citrate, 15-25 g / L sodium acetate, 15-25 g / L sodium hypophosphite, 0.1-0.4 g / L graphene oxide, 0.4-0.5 g / L sodium dodecylbenzene sulfonate, and the solvent is deionized water. In the present invention, the content of each in the specific embodiment is the same as the content of each component in the aforementioned basic plating solution and chemical plating solution, and will not be repeated here.
[0067] The present invention also provides a method for preparing a Ni-P-Gr chemical plating layer, comprising the following steps: placing a substrate in a chemical plating solution prepared by the preparation method described in the above technical solution, performing chemical plating, and forming a Ni-P-Gr chemical plating layer on the surface of the substrate.
[0068] In the present invention, the substrate includes a stainless steel substrate or a carbon steel substrate; the stainless steel substrate preferably includes a martensitic stainless steel substrate, an austenitic stainless steel substrate or a ferritic stainless steel substrate; the martensitic stainless steel substrate preferably includes 0Cr13Ni5Mo, 0Cr16Ni5Mo or 1Cr17Ni2.
[0069] In the present invention, the stainless steel substrate is preferably subjected to acid-base degreasing, sensitization treatment, activation treatment and reduction treatment in sequence before use.
[0070] In the present invention, the acid-base degreasing preferably further comprises: grinding, ethanol washing, water washing (referred to as the first water washing) and drying (referred to as the first drying) of the stainless steel substrate. In the present invention, the grinding is preferably performed using sandpaper No. 80, No. 240, No. 400, No. 800 and No. 1000 in sequence until the substrate is smooth and flat without scratches. In the present invention, the drying preferably comprises air drying.
[0071] In the present invention, the acid-base degreasing includes ultrasonic cleaning, alkaline cleaning using an alkaline degreasing agent, water washing (recorded as the third water washing), acid neutralization, secondary water washing (recorded as the fourth water washing) and drying (recorded as the second drying) in sequence. In the present invention, the cleaning agent used in the ultrasonic cleaning preferably includes anhydrous ethanol or soapy water. In the present invention, the time of the ultra-clear cleaning is preferably 10 to 20 minutes, more preferably 15 minutes; the temperature of the ultrasonic cleaning is preferably room temperature. After completing the ultrasonic cleaning, the present invention preferably also includes water washing (recorded as the second water washing), and then acid-base degreasing, the second water washing preferably includes water rinsing, the temperature of the second water washing is preferably room temperature, the time of the second water washing is preferably 1 to 3 minutes, more preferably 1 to 2 minutes; the water used for the water washing preferably includes deionized water. In the present invention, the alkaline degreasing agent preferably includes 25-35 g / L of alkali metal hydroxide, which may be 25 g / L, 26 g / L, 27 g / L, 28 g / L, 29 g / L, 30 g / L, 31 g / L, 32 g / L, 33 g / L, 34 g / L or 35 g / L in a specific embodiment of the present invention, and the alkali metal hydroxide preferably includes NaOH and / or KOH; 15-25 g / L of alkali metal carbonate, which may be 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L, 20 g / L, 21 g / L, 22 g / L, 23 g / L, 24 g / L or 25 g / L in a specific embodiment of the present invention, and the alkali metal carbonate preferably includes Na2CO3 or K2CO3; 15-25 g / L of alkali metal phosphate , in a specific embodiment of the present invention, it can be 15g / L, 16g / L, 17g / L, 18g / L, 19g / L, 20g / L, 21g / L, 22g / L, 23g / L, 24g / L or 25g / L, and the alkali metal phosphate preferably includes Na3PO4 and / or K3PO4; the non-ionic surfactant is 0.5-1.5g / L, in a specific embodiment of the present invention, it can be 0.5g / L, 0.6g / L, 0.7g / L, 0.8g / L, 0.9g / L, 1g / L, 1.1g / L, 1.1.g / L, 1.3g / L, 1.4g / L or 1.5g / L, and the non-ionic surfactant preferably includes OP-10 (polyoxyethylene octylphenol ether-10); the solvent of the alkaline degreasing agent is preferably anhydrous ethanol. In the present invention, the alkali washing is preferably carried out under ultrasonic conditions, the alkali washing time is preferably 25 to 35 minutes, more preferably 30 minutes; the alkali washing temperature is preferably room temperature. In the present invention, the third water washing preferably includes water rinsing, and the purpose of the third water washing is to remove residual alkaline degreasing agent and impurities.In the present invention, the acid neutralization preferably uses a pH adjuster to adjust the pH value to 6.9-7.1 (in a specific embodiment of the present invention, the pH value can be 6.9, 7 or 7.1); the pH adjuster preferably includes a mixed solution of HCl aqueous solution and ammonia water; the concentration of the HCl aqueous solution is preferably 12 mol / L, and the concentration of the ammonia aqueous solution is 13.38 mol / L. In the present invention, the fourth water washing preferably includes water rinsing, the purpose of which is to remove residues in the acidic solution and ensure that the substrate surface is clean. In the present invention, the second drying preferably includes blowing with compressed air or drying naturally.
[0072] In the present invention, the composition of the sensitizing solution used in the sensitization treatment preferably includes SnCl2, HCl aqueous solution and deionized water. The content of SnCl2 in the sensitizing solution is preferably 8-12 g / L, and in a specific embodiment of the present invention, it can be 8 g / L, 8.5 g / L, 93 g / L, 9.5 g / L, 10 g / L, 10.5 g / L, 11 g / L or 12 g / L; the HCl aqueous solution and deionized water in the sensitizing solution The volume ratio of the sub-water is preferably 7 to 9:1; in a specific embodiment of the present invention, it can be 7:1, 7.1:1, 7.2:1, 7.3:1, 7.4:1, 7.5:1, 7.6:1, 7.7:1, 7.8:1, 7.9:1, 8:1, 8.1:1, 8.2:1, 8.3:1, 8.4:1, 8.5:1, 8.6:1, 8.7:1, 8.8:1, 8.9:1 or 9:1. In the present invention, the concentration of the HCl aqueous solution is preferably 12 mol / L. In the present invention, the temperature of the sensitization treatment is preferably room temperature, and the time is preferably 4 to 6 minutes, and in a specific embodiment of the present invention, it can be 4 minutes, 4.5 minutes, 5 minutes, 5.5 minutes or 6 minutes. Through the sensitization treatment, the reducing substance Sn that can serve as a catalyst for the chemical plating reaction is adsorbed on the surface of the substrate. 2+ , providing catalytic active centers for subsequent chemical plating reactions.
[0073] In the present invention, the composition of the activation solution used in the activation treatment preferably includes PdCl2, ethanol and deionized water. The content of PdCl2 in the activation solution is preferably 0.3-0.6 g / L, and in a specific embodiment of the present invention, it can be 0.3 g / L, 0.4 g / L, 0.5 g / L or 0.6 g / L; the volume ratio of ethanol to deionized water in the activation solution is preferably 2-3:1, and in a specific embodiment of the present invention, it can be 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3:1; the temperature of the activation treatment is preferably room temperature, and the time is preferably 1.5-2.5 min, more preferably 2 min. The present invention introduces precious metal ions Pd on the surface of the substrate through activation treatment. 2+ , Pd 2+ Can be sensitized by the reducing substance Sn in the sensitizer 2 + Reduced into solid metal particles to form catalytically active centers. The catalytically active centers generated during the activation process can enhance the bonding force between the chemical plating layer and the substrate, thereby enhancing the adhesion ability of the chemical plating layer.
[0074] In the present invention, the composition of the reducing solution used in the reduction treatment preferably includes sodium hypophosphite and deionized water, and the content of sodium hypophosphite in the reducing solution is preferably 25-35 g / L, and in specific embodiments, it can be 25 g / L, 26 g / L, 27 g / L, 28 g / L, 29 g / L, 30 g / L, 31 g / L, 32 g / L, 33 g / L, 34 g / L or 35 g / L. In the present invention, the temperature of the reduction treatment is preferably room temperature, and the time is preferably 25-35 s, more preferably 30 s. The present invention performs the reduction treatment in order to absorb ions that affect the stability of the chemical plating solution.
[0075] In the present invention, the temperature of the chemical plating is preferably 70-90°C, and in a specific embodiment of the present invention, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C; the time of the chemical plating is preferably 2-3h, and in a specific embodiment of the present invention, it can be 120min, 125min, 130min, 135min, 140min, 145min, 150min, 155min, 160min, 165min, 170min, 175min or 180min; the chemical plating is preferably carried out under stirring conditions.
[0076] After the chemical plating is completed, the present invention preferably further comprises: washing the plated part with water and then drying it. In the present invention, the water used for washing preferably comprises deionized water. In the present invention, the drying temperature is preferably 45 to 55° C., more preferably 50 to 55° C. The drying time is preferably 30 to 40 minutes, more preferably 35 minutes.
[0077] The method for preparing the Ni-P-Gr chemical plating layer provided by the invention has simple process and low cost. The prepared Ni-P-Gr chemical plating layer has high hardness, good wear resistance and strong bonding force with a substrate.
[0078] The present invention also provides a Ni-P-Gr chemical plating layer obtained by the preparation method described in the above technical solution.
[0079] The present invention also provides the application of the Ni-P-Gr chemical plating layer described in the above technical solution in the field of metal surface modification, wherein the metal preferably includes a ferrous metal, and more preferably is martensitic stainless steel.
[0080] In order to further illustrate the present invention, the chemical plating solution and its preparation method, the Ni-P-Gr chemical plating layer and its preparation method and application provided by the present invention are described in detail below in combination with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0081] In the following examples, the test materials used are as follows.
[0082] (1) Test material: 0Cr13Ni5Mo ultra-low carbon martensitic stainless steel was selected as the matrix, and the specimen was a Φ25 mm × 2 mm circular sheet. The chemical composition of the matrix material is shown in Table 1.
[0083] Table 10Chemical composition of Cr13Ni5Mo stainless steel (wt.%)
[0084] element C Si Mn Cr Ni Mo content ≤0.03 <0.3 0.4~1.0 12~14 4.0~6.0 0.5~10
[0085] 0.2 g / L and 0.4 g / L graphene oxide deionized water suspensions were prepared and placed for 24 hours before use in subsequent experiments.
[0086] (2) The names and specifications of the main test equipment are shown in Table 2.
[0087] Table 2 Main equipment and instruments
[0088] Instrument Name model Instrument Name model Digital electronic balance FA2004 Microhardness tester HYST-1000 Electric heating blast drying oven WGL-65B X-ray diffractometer DX-2700B High speed homogenizer RCD-1A Scanning electron microscopy SU5000 Ultrasonic cleaning machine F-020ST Metallographic microscope AX10 Single-station magnetic stirring water bath SN-NWS-2DJ pH pen meter SX-610 High temperature friction and wear testing machine MPT-3G
[0089] (3) Performance testing methods
[0090] The structural analysis of Ni-P-Gr chemical plating involves the following main contents: microstructure observation and phase analysis, and the performance test covers aspects such as wear resistance, bonding strength and microhardness. The test method is as follows
[0091] (3.1) Microstructure observation and phase analysis methods
[0092] Metallographic analysis: Use a mobile phone to adjust the light, take a photo on A4 white paper and capture the photo to save the macroscopic Ni-P-Gr chemical plating metallographic structure. Use Zeiss AX10 metallographic microscope to photograph and study the metal structure of the microscopic coating. Place the sample prepared in the embodiment on the stage, adjust it to the preset magnification and scale, adjust the light brightness, focus through the coarse and fine adjustment knobs, and then take a photo of the microscopic coating structure.
[0093] Scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS): Self-coagulated dental tray powder was used to mount the cross-section of the plated parts containing Ni-P-Gr chemical plating, and the samples were ground and polished. The thickness and surface characteristics of the coating were studied using a SU-5000 scanning electron microscope (SEM). The chemical composition of the coating was analyzed by elemental analysis using an energy dispersive X-ray spectrometer (EDS) equipped with the SEM, and the cross-section was observed by line scanning to analyze the chemical composition of the surface and cross-section as well as the element distribution and proportion.
[0094] X-ray diffraction phase analysis (XRD): The surface of the plated parts containing Ni-P-Gr chemical plating was analyzed by X-ray diffraction using a DX-2700B X-ray diffractometer. The test conditions included: diffraction angle of 10-90°, scanning speed of 0.02° / s, sampling time of 0.3, tube voltage of 40 kV, and tube current of 30 mA.
[0095] (3.2) Hardness test: The microhardness test of the plated parts containing Ni-P-Gr chemical plating was carried out using a NHV2000 microhardness tester, with the loading time set to 10 seconds and the loading force set to 2.942 N. Five points were randomly selected on the surface of the coating, the data were recorded and the average value was taken.
[0096] (3.3) Friction and wear test: The reciprocating friction tester is a method that measures the average friction coefficient of the coating by moving the friction head at a certain speed on the surface of the sample fixed on the horizontal workbench under a specific load. In the present invention, the MPT-3G high temperature friction and wear tester is used to determine the friction coefficient of the Ni-P-Gr chemical coating. The test force is set to 1N, the test temperature is 0℃, the test speed is 50r / min, and the test time is 10min.
[0097] (3.4) Adhesion test: According to GB / T13913-92 standard, the adhesion of Ni-P-Gr chemical plating is evaluated by thermal shock test. The sample is kept in a WGL-65B electric heating blast drying oven with a set temperature of 250±10℃ for 1 hour, then quickly taken out and immersed in cold water. The above process needs to be repeated 10 times. If there are no bubbles or flaking in the coating through a magnifying glass, it can be judged that the coating has good adhesion.
[0098] Example 1
[0099] 1. Sample pretreatment
[0100] Prefabricated specimens: Use a digital cutting machine to grind the cut specimens from 0Cr13Ni5Mo stainless steel rods with 80, 240, 400, 800, and 1000 sandpapers in turn until they are smooth and free of scratches. Then, wash them with alcohol and deionized water respectively, and air-dry them to obtain the matrix specimens for later use.
[0101] 1.1 Acid and alkali degreasing (performed at room temperature)
[0102] 1.1.1 Ultrasonic cleaning: After polishing, add anhydrous ethanol to the substrate specimen and clean it in an ultrasonic cleaner for 15 minutes, and finally rinse it with deionized water for 1 minute.
[0103] 1.1.2 Alkaline degreasing: soak in alkaline degreasing agent and wash in ultrasonic cleaning machine for 30 minutes; alkaline degreasing agent composition: NaOH 30g / L, Na2CO320g / L, Na3PO420g / L, OP-101g / L, the solvent is anhydrous ethanol.
[0104] 1.1.3 Water washing: After taking the specimen out of the alkaline degreaser, rinse it with running water to remove the residual degreaser and impurities.
[0105] 1.1.4 Acid neutralization: Soak the specimen in 12 mol / L HCl aqueous solution for 30 s.
[0106] 1.1.5 Secondary water washing: Rinse the specimen again with running water to remove the residue in the acid solution and ensure the surface is clean.
[0107] 1.1.6 Drying: Take the specimen out of the water, blow it dry with compressed air or let it dry naturally to obtain the acid-base degreasing matrix.
[0108] 1.2 Sensitization, activation and reduction treatment
[0109] 1.2.1 Sensitization treatment
[0110] The acid-base degreased substrate was placed in a sensitizing solution and sensitized for 5 minutes at room temperature. After that, it was washed with anhydrous ethanol and dried with a hair dryer to obtain a sensitized substrate. The sensitizing solution consists of: SnCl2 10g / L, HCl aqueous solution 12mol / L, and the solvent is deionized water. The volume ratio of HCl aqueous solution to deionized water in the sensitizing solution is 7-9:1. Through the sensitization treatment, the metal surface is adsorbed with the reducing substance Sn that can serve as a catalyst for the chemical plating reaction. 2+ , providing catalytic active centers for subsequent chemical plating reactions.
[0111] 1.2.2 Activation treatment: Place the sensitized substrate in the activation solution, activate it at room temperature for 2 minutes, then wash it with anhydrous ethanol and dry it with a hair dryer to obtain the activated substrate. The activation solution consists of PdCl2 0.3-0.6 g / L, and the solvent is ethanol and deionized water in a volume ratio of 2-3:1. Through the activation treatment, the precious metal ion Pd is introduced on the metal surface. 2 + , Pd 2+ Can be sensitized by the reducing substance Sn in the sensitizer 2+ Reduced to solid metal particles, forming catalytic active centers. The catalytic active centers generated during the activation process can enhance the bonding force between the chemical plating layer and the substrate, thereby enhancing the adhesion ability of the plating layer.
[0112] 1.2.3 Reduction treatment: Place the activated substrate in the reduction solution, activate it at room temperature for 30 seconds, wash the sample with anhydrous ethanol and dry it with a hair dryer to obtain the reduced substrate. The reduction solution consists of 30 g / L sodium hypophosphite and deionized water as the solvent. The purpose of the reduction treatment is to absorb ions that affect the stability of the plating solution.
[0113] 2. Chemical plating
[0114] Preparation of chemical plating solution: According to the formula in Table 3, nickel sulfate, sodium hypophosphite, sodium acetate, sodium citrate and graphene oxide are placed in deionized water and mixed until completely dissolved, respectively, to obtain nickel sulfate solution, sodium hypophosphite solution, sodium acetate solution, sodium citrate solution and graphene oxide solution; first pour the nickel sulfate solution into the sodium citrate solution, stir it thoroughly and then pour it into the sodium acetate solution to obtain a mixed solution; add the sodium hypophosphite solution, add the graphene oxide solution soaked in deionized water for 24 hours, and stir until the mixture is uniform. Use 12mol / L HCl aqueous solution to adjust the pH value to 4.2 to obtain a basic plating solution. Add SDBS (sodium dodecylbenzene sulfonate) to the basic plating solution, use a high-speed homogenizer at room temperature at a speed of 15000r / min for homogenization for 10min, and use ultrasonic power (180W) to ultrasonically disperse the chemical plating solution containing SDBS for 35min at room temperature to obtain a chemical plating solution.
[0115] Table 3 Chemical plating solution
[0116] Pharmacy Content (g / L) Nickel sulfate 30 Sodium hypophosphite 20 Sodium acetate 20 Sodium Citrate 10 Graphene oxide 0.1 Sodium dodecylbenzenesulfonate 0.42
[0117] Chemical plating: The reduced substrate is clamped in a beaker of chemical plating solution and a stirring rotor is placed in it, which is then placed in a water bath at a constant temperature of 80°C for 2 hours. After plating, it is washed with deionized water and dried in a drying oven at 55°C for 30 minutes to form a Ni-P-Gr chemical plating layer on the surface of the reduced 0Cr13Ni5Mo stainless steel.
[0118] Embodiments 2 to 36
[0119] The differences between the preparation conditions of Example 1 and those of Example 1 are shown in Table 4, and the other preparation conditions are the same as those of Example 1.
[0120] Table 4 Preparation conditions of the examples
[0121]
[0122] Test Example 1
[0123] The influence of ultrasonic power and ultrasonic time on Ni-P-Gr chemical plating (this part of the process mainly explores the strength of the bonding between the coating and the substrate and the micromorphology of the coating, in preparation for subsequent experiments to change the amount of graphene oxide added), where the graphene oxide content is 0.2g / L.
[0124] (1) Macromorphology analysis
[0125] Figure 1 The macroscopic organization pictures of Ni-P-Gr chemical plating prepared under different ultrasonic powers and times are shown as follows: a) 180W / 35min; b) 180W / 45min; c) 140W / 35min, d) 140W / 45min; e) 100W / 35min, f) 100W / 45min; g) 180W / 55min; h) 140W / 55min; i) 100W / 55min. It can be seen that from the perspective of ultrasonic power, the surface of Ni-P-Gr chemical plating under 100W and 140W is black and the overall surface is relatively flat; the sample under 180W has too high ultrasonic power, and the dispersion of graphene oxide in the plating solution is not uniform, which makes the surface of Ni-P-Gr chemical plating uneven, affecting the overall uniformity of the coating.
[0126] (2) Phase analysis
[0127] Figure 2XRD diffraction pattern of Ni-P-Gr chemical coating with ultrasonic power of 140W and ultrasonic time of 35min. In X-ray diffraction analysis, it is preliminarily proved that graphene oxide exists on Ni-P-Gr chemical coating, and it is observed that when the 2θ angle is 26.3167°, the diffraction peak of graphene oxide only appears slightly. This phenomenon shows that the content of graphene oxide in chemical coating is low, resulting in weak signal intensity of diffraction peak. In addition, the obvious sharp diffraction peak of nickel (Ni) can be clearly seen, which shows that chemical coating has a crystalline structure. Since the penetration thickness of X-ray diffractometer is usually greater than 20μm, it can be seen that the matrix Fe peak has sharp diffraction peaks when 2θ is 65.504° and 82.669°, respectively. In summary, graphene oxide is present in the coating.
[0128] (3) Cross-sectional morphology analysis
[0129] Figure 3 The cross-sectional SEM morphology of Ni-P-Gr chemical plating under different ultrasonic powers and times, among which the left picture is 140W / 45min; the right picture is 100W / 35min. It can be seen from the figure that the Ni-P-Gr chemical plating with ultrasonic power of 140W and ultrasonic time of 45min is thicker, reaching 14.25μm. It can be clearly seen that graphene oxide is interwoven with Ni and P, and the Ni-P-Gr chemical plating has a better bonding effect with the substrate, without defects such as cracks and pores.
[0130] Figure 4 The following are the element diffraction peak intensity distribution diagrams of the cross-section of the Ni-P-Gr chemical plating layer under different ultrasonic powers and times, among which the left figure is 140W / 45min; the right figure is 100W / 35min. As can be seen from the figure, the diffraction peak intensity of the Ni peak of the cross-section under 140W / 45min is higher than that of 100W / 35min, which shows that the chemical plating process of the former is better. This is because ultrasonic treatment helps to disperse graphene oxide in the plating solution, thereby preventing it from agglomerating. Therefore, longer ultrasonic time and higher ultrasonic power can more effectively disperse graphene oxide and make it more evenly distributed in the plating solution, which is conducive to the uniform growth of the Ni-P-Gr chemical plating layer and increases the thickness of the Ni-P-Gr chemical plating layer.
[0131] (4) Hardness analysis
[0132] Figure 5The microhardness of Ni-P-Gr chemical plating under different ultrasonic powers and times. It can be seen that the hardness of Ni-P-Gr chemical plating under 140W and 180W ultrasonic powers first increases and then decreases with time, while the ultrasonic power of 120W is the opposite. Overall, the highest hardness is mainly concentrated in the ultrasonic time of 45min. This is because ultrasonic treatment helps the dispersion of graphene oxide in the plating solution. If the ultrasonic treatment time is too short, graphene oxide cannot be fully dispersed, resulting in uneven distribution of graphene oxide in the coating; conversely, too long ultrasonic treatment time causes graphene oxide to agglomerate or structurally destroy, affecting its enhancement effect. A moderate ultrasonic time can just achieve the best dispersion effect, so 45min is a moderate ultrasonic time.
[0133] The coating with an ultrasonic power of 180 W and an ultrasonic time of 45 min has the highest microhardness, with a maximum hardness of 814.558 HV. It can be seen that the ultrasonic power is just enough to make the graphene oxide reach a good dispersion state in the plating solution without destroying the structure of the graphene oxide or causing excessive agglomeration. Appropriate dispersibility helps the graphene oxide to be evenly distributed in the coating, thereby improving the hardness.
[0134] (5) Binding strength analysis
[0135] Thermal shock tests were carried out on the 9 prepared plated parts (ultrasonic power and time were as follows: 180W / 35min, 180W / 45min, 140W / 35min, 140W / 45min, 100W / 35min, 100W / 45min, 180W / 55min, 140W / 55min, 100W / 55min).
[0136] Figure 6 These are samples with cracks and bubbles in the thermal shock test. The ultrasonic parameters in the left picture are 180W / 45min; the ultrasonic parameters in the right picture are 180W / 55min. As can be seen from the figure, in the fourth hot and cold cycle, the coating of the sample with an ultrasonic power of 180W and an ultrasonic time of 45min cracked, while the coating of the sample with an ultrasonic power of 140W and an ultrasonic time of 55min had bubbles. After 10 hot and cold cycles, the coating on the surface of the other 8 samples was intact, without any falling off or pulling up, indicating that other chemical coatings were well combined with the 0Cr13Ni5Mo stainless steel substrate. Therefore, it can be judged that the above two groups are not the best process parameters.
[0137] According to the above test analysis, the Ni-P-Gr chemical plating layer with an ultrasonic power of 180W and an ultrasonic time of 45min has the highest microhardness, but cracks appear in the thermal shock test, so it is not the best process parameter. The microhardness of the coating with an ultrasonic power of 140W and an ultrasonic time of 45min is second only to that with good bonding strength, so this process parameter is determined to be the best process parameter.
[0138] Test Example 2
[0139] Effect of graphene oxide addition amount (0.1g / L, 0.2g / L, 0.3g / L and 0.4g / L) on Ni-P-Gr chemical plating, where the ultrasonic power is 140W and the ultrasonic time is 45min.
[0140] (1) Macromorphology analysis
[0141] Figure 7 The macroscopic morphology of the Ni-P-Gr chemical plating layer with different addition amounts of graphene oxide, from left to right, the addition amounts of graphene oxide are 0.1g / L, 0.2g / L, 0.3g / L and 0.4g / L. As can be seen from the figure, with the increase of the addition ratio of graphene oxide, the surface roughness of the Ni-P-Gr chemical plating layer gradually increases, and the surface of graphene oxide is the roughest after adding 0.4g / L. This is because the increase of graphene oxide will cause its dispersibility in the plating solution to deteriorate, thereby causing agglomeration between graphene oxide sheets, and this agglomerate forms larger particles or agglomerates in the coating, increasing the surface roughness.
[0142] (2) Metallographic structure analysis
[0143] Figure 8 The surface morphology of Ni-P-Gr chemical plating with different additions of graphene oxide was taken by AX10 metallographic microscope. The left picture of the first row is 0.1g / L, the right picture of the first row is 0.2g / L, the left picture of the second row is 0.3g / L, and the right picture of the second row is 0.4g / L. It can be seen that when the content of graphene oxide gradually increases, more pores and defects are introduced into the surface of the coating, thereby increasing the surface roughness. This shows that the increase of graphene oxide is accompanied by its poor dispersion in the plating solution, thereby forming agglomerates. These agglomerates will not be evenly wrapped in the Ni-P coating during the deposition process, but will form protrusions on the surface, resulting in an increase in the surface roughness of the Ni-P-Gr chemical plating.
[0144] (3) Cross-sectional morphology analysis
[0145] Fig. 9The cross-sectional SEM morphology of Ni-P-Gr chemical plating at different graphene oxide additions, the first row left picture is 0.1g / L, the first row right picture is 0.2g / L, the second row left picture is 0.3g / L, and the second row right picture is 0.4g / L. It can be seen from the figure that with the increase of graphene oxide content, the thickness of the chemical plating layer shows a trend of first increasing and then decreasing. The coating thickness of graphene oxide additions of 0.1g / L and 0.2g / L is similar, the surface is smooth and flat, and there are no defects, but the coating is weakly bonded to the substrate and there are gaps. This is because when the amount of graphene oxide added is low, due to the insufficient dispersibility of graphene oxide in the plating solution, its distribution in the coating is uneven, thereby affecting the thickness of the coating and its bonding with the substrate. In addition, it may be due to the insufficient interaction between graphene oxide and Ni-P in the plating solution to form a stable structure. When the addition amount of graphene oxide increases to 0.3g / L, the coating thickness increases significantly to 14.32μm, and the bonding between the coating and the substrate is improved. This is due to the improved dispersibility of graphene oxide in the plating solution and the enhanced interaction between graphene oxide and Ni-P, which promotes the uniform distribution of graphene oxide in the coating, thereby increasing the thickness of the coating and improving the bonding with the substrate. When the content of graphene oxide increases to 0.4g / L, the coating thickness decreases to 11.03μm, but the coating effect is poor and the interface with the substrate is not obvious. This is because the increase in graphene oxide causes its dispersibility in the plating solution to deteriorate and form agglomerates, thereby forming defects in the coating and reducing the uniformity and thickness of the coating.
[0146] Fig.10 The EDS thermal field spectrum image and element distribution map of Ni-P-Gr chemical plating layer with a graphene oxide addition amount of 0.1g / L. Fig.11 The EDS thermal field spectrum image and element distribution map of Ni-P-Gr chemical plating layer with a graphene oxide addition of 0.2g / L. Fig.12 The EDS thermal field spectrum image and element distribution map of Ni-P-Gr chemical plating layer with a graphene oxide addition of 0.3g / L. Fig.13 This is the EDS thermal field energy spectrum image and element distribution map of the Ni-P-Gr chemical plating layer with a graphene oxide addition amount of 0.4g / L.
[0147] Table 5 EDS distribution chart total number spectrum
[0148]
[0149] Depend on Figure 10 to Figure 13As shown in Table 5, the main elements contained in the chemical plating layer are C, Ni, and P, so nickel, phosphorus, and graphene oxide are co-deposited in the chemical plating solution to generate a Ni-P-Gr chemical plating layer. It can be seen from the element distribution diagram that the dispersion of nickel and graphene oxide is relatively uniform, and the surface of the coating under 0.1g / L and 0.3g / L is in the form of holes and lumps. It can be concluded from the element distribution diagram that the lumpy part is phosphorus, and due to the secondary plating carried out in the experiment, the graphene oxide deposited on the surface of the substrate is covered, resulting in a smaller proportion of the C element under Table 5. In summary, it can be further proved that graphene oxide exists on the surface of the coating.
[0150] (4) Hardness analysis
[0151] Fig.14 The microhardness of the surface of Ni-P-Gr chemical plating layer with different addition amounts of graphene oxide. As the content of graphene oxide increases, the hardness of the chemical plating layer fluctuates up and down. When the addition amount of graphene oxide is 0.3g / L, the microhardness of the chemical plating layer reaches 936.036HV, which is 25.05% higher than the coating with 0.2g / L graphene oxide content. This is mainly because the graphene oxide is more evenly dispersed in the matrix, thus playing a role of dispersion strengthening. When the addition amount of graphene oxide increases to 0.4g / L, the micro-average hardness does not continue to rise, but a certain decline occurs. The uneven hardness distribution can also be seen from the standard deviation. This is because with the increase of the content of graphene oxide in the plating solution, its specific surface area is larger, and graphene oxide thus appears to agglomerate at the grain boundary. The agglomerated graphene oxide cannot improve the hardness of the coating, but will show the characteristics of "defects", so that the dispersion distribution cannot be achieved, resulting in a decrease in microhardness.
[0152] (5) Friction and wear performance
[0153] Fig.15 The wear metallographic structure morphology of Ni-P-Gr chemical plating with different addition amounts of graphene oxide, among which the left picture of the first row is 0.1g / L, the right picture of the first row is 0.2g / L, the left picture of the second row is 0.3g / L, and the right picture of the second row is 0.4g / L. From the microscopic wear morphology of the coating surface, it can be observed that the surface shows certain wear marks, and there is a certain amount of adhesion and furrowing, indicating that abrasive wear and adhesive wear exist during the wear process. In addition, the adhesion points on the surface of the coating with 0.2g / L graphene oxide addition are relatively more dispersed, while the wear of the friction chemical plating with 0.3g / L is relatively less, with only a small number of adhesion points, indicating that abrasive wear has occurred.
[0154] Fig.16The graph of the friction coefficient of Ni-P-Gr chemical plating with different graphene oxide additions versus abrasion time shows that the friction coefficient curve is relatively gentle when the graphene oxide addition is 0.3g / L and 0.4g / L, and the average friction coefficient of 0.2g / L is the smallest but the curve fluctuates greatly, which indicates that the graphene oxide content may be at the optimal critical concentration, and graphene oxide begins to form a relatively continuous dispersed phase, but has not yet reached the level of forming a uniform and stable coating, resulting in a decrease in the friction coefficient but a large fluctuation. In addition, because its wear mechanism is different from that of 0.3g / L and 0.4g / L, there is more adhesive wear or abrasive wear, and changes in the wear mechanism will lead to fluctuations in the friction coefficient.
[0155] Fig.17 The following is a comparison of the weight loss before and after friction and wear of Ni-P-Gr chemical plating with different graphene oxide additions. It can be seen from the figure that the friction and wear amount of the graphene oxide addition of 0.2g / L is the largest, reaching 2.4mg. With the increase of graphene oxide, the wear amount of the coating increases first and then decreases. When the addition of graphene oxide is 0.3g / L, the wear amount reaches the minimum value of 0.3mg, which is 87.5% lower than the wear amount of 0.2g / L graphene oxide. This is because graphene oxide has a layered structure and forms a certain lubrication effect in the coating. As the content increases, this lubrication effect gradually increases until it reaches an optimal point of 0.3g / L, thereby providing the best wear resistance.
[0156] (6) Binding strength analysis
[0157] After 10 rounds of thermal shock test, the four groups (graphene oxide addition amount is 0.1g / L, 0.2g / L, 0.3g / L and 0.4g / L) of Ni-P-Gr chemical plating did not show peeling and cracking. The thermal shock test results show that the Ni-P-Gr chemical plating did not show obvious bubbling, cracking or shedding, which further confirms that the Ni-P-Gr chemical plating prepared by the present invention has good bonding with the substrate.
[0158] According to the above test analysis, the Ni-P-Gr chemical plating layer with 0.3g / L graphene oxide addition has higher hardness (936.036HV), less wear (0.3mg) and good bonding strength, so 0.3g / L graphene oxide addition is the best addition amount.
[0159] In summary, the present invention uses 0Cr13Ni5Mo as a substrate and performs chemical plating of Ni-P-Gr chemical plating on its surface. The focus is on studying the effects of ultrasonic dispersion time, ultrasonic power, and changes in the amount of graphene oxide added on the structure and performance of the coating. The microstructure morphology of the coating under different process conditions was observed by scanning electron microscopy, the physical phase of the coating was determined by XRD, the microhardness and friction and wear properties under different process conditions were tested, and the bonding strength of the coating was tested. The results show that: (1) Through a comprehensive evaluation of methods such as microhardness test, friction and wear test, and thermal shock test, it is confirmed that the Ni-P-Gr chemical plating has good wear resistance and strong bonding with the substrate. (2) Ultrasonic power and time have a significant effect on the dispersibility of graphene oxide in the plating solution. When the ultrasonic power is 140W and the ultrasonic time is 45min, the graphene oxide is most evenly dispersed, and the obtained coating structure is the densest and the hardness is the highest. (3) The increase in the amount of graphene oxide added will lead to an increase in the surface roughness of the coating, which is due to the deterioration of the dispersibility of graphene oxide in the plating solution, causing agglomeration. (4) The optimal addition amount of graphene oxide is 0.3 g / L. At this time, the microhardness of the chemically plated coating reaches 936.036 HV and the wear amount is reduced to 0.3 mg, showing excellent wear resistance and good bonding strength.
[0160] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a chemical plating solution, comprising the following steps: Add nickel sulfate, sodium citrate, sodium acetate, sodium hypophosphite and graphene oxide, and adjust the pH value to 4-4.5 to obtain a basic plating solution; the content of graphene oxide in the basic plating solution is 0.1-0.4 g / L; The base plating solution is mixed with sodium dodecylbenzene sulfonate, homogenized and then ultrasonically dispersed to obtain a chemical plating solution; the power of the ultrasonic dispersion is 100 to 180 W, and the time is 35 to 55 minutes.
2. The preparation method according to claim 1, characterized in that: The composition of the basic plating solution includes: 25-35 g / L nickel sulfate, 8-12 g / L sodium citrate, 15-25 g / L sodium acetate, 15-25 g / L sodium hypophosphite, 0.1-0.4 g / L graphene oxide, and the solvent is deionized water; The graphene oxide is soaked in deionized water before use.
3. The preparation method according to claim 1 or 2, characterized in that: The rotation speed of the homogenization treatment is 12000-16000 r / min, and the time is 10-15 min.
4. The chemical plating solution prepared by the preparation method according to any one of claims 1 to 3, wherein the content of graphene oxide in the chemical plating solution is 0.1 to 0.4 g / L.
5. The chemical plating solution according to claim 4, characterized in that: Composition includes: Nickel sulfate 25-35 g / L, sodium citrate 8-12 g / L, sodium acetate 15-25 g / L, sodium hypophosphite 15-25 g / L, graphene oxide 0.1-0.4 g / L, sodium dodecylbenzene sulfonate 0.4-0.5 g / L, and the solvent is deionized water.
6. A method for preparing a Ni-P-Gr chemical plating layer, comprising the following steps: The substrate is placed in the chemical plating solution of claim 4 or 5 to perform chemical plating to form a Ni-P-Gr chemical plating layer on the surface of the substrate.
7. The preparation method according to claim 6, characterized in that: The substrate comprises a stainless steel substrate or a carbon steel substrate; The stainless steel substrate includes a martensitic stainless steel substrate, an austenitic stainless steel substrate or a ferritic stainless steel substrate; The stainless steel substrate is first subjected to acid-base degreasing, sensitization treatment, activation treatment and reduction treatment in sequence before use; The sensitizing solution used in the sensitization treatment includes SnCl2, HCl aqueous solution and deionized water, the content of SnCl2 in the sensitizing solution is 8-12 g / L, and the volume ratio of HCl aqueous solution to deionized water is 7-9:1; the temperature of the sensitization treatment is room temperature, and the time is 4-6 minutes; The activation solution used in the activation treatment includes PdCl2, ethanol and deionized water, the content of PdCl2 in the activation solution is 0.3-0.6 g / L, and the volume ratio of ethanol to deionized water is 2-3:1; the temperature of the activation treatment is room temperature, and the time is 1.5-2.5 min; The reducing solution used in the reduction treatment includes sodium hypophosphite and deionized water, and the content of sodium hypophosphite in the reducing solution is 25-35 g / L; the temperature of the reduction treatment is room temperature, and the time is 25-35 seconds.
8. The preparation method according to claim 6 or 7, characterized in that: The temperature of the chemical plating is 70-90° C., the time is 2-3 hours, and the chemical plating is carried out under stirring conditions.
9. The Ni-P-Gr chemical plating layer obtained by the preparation method according to any one of claims 6 to 8.
10. Use of the Ni-P-Gr chemical plating layer according to claim 9 in the field of metal surface modification.
Citation Information
Cited By
Chemical blackening process of stainless steel and application
CN119824403A
A Chemical Blackening Process for Stainless Steel and Its Application
CN119824403B